Shifting Power-Centres of Semi-Presidentialism: Exploring Executive Coordination in Lithuania. Issue 4 (4th December 2017) - Raunio, Tapio; Sedelius, Thomas
Abstract : Despite more than two decades of research on semi-presidential regimes, we still know very little about the actual coordination between the president and the prime minister. Through an in-depth analysis of Lithuanian semi-presidentialism, this article underscores the importance of institutional design on intra-executive balance of power. Drawing primarily on interviews with top-level civil servants and office-holders, it argues that in the absence of written rules or other strong norms guiding intra-executive coordination, presidents enjoy more discretion in designing their own modes of operation. Coordination depends on the initiative of the president, with ad hoc practices further weakening the position of the prime minister. While Lithuanian semi-presidentialism has functioned smoothly, the personality-centred politics commonly found in Central and East European countries create favourable conditions for presidential activism.